Estimation the Number of Visitor of E-Commerce Website by Artificial Neural Networks During Covid19 in Turkey. - Kayakuş, Mehmet; Çevik, Kerim Kürşat (Electronic Turkish Studies, 2020)
Developments in the field of internet technology affect human life in every way and cause their daily lives to positively change over time. One of the conveniences and positive effects provided by the internet has been e-commerce technology that has brought a new perspective to commerce and shopping for both the operator and client. Thanks to e-commerce, people can shop online by using websites and mobile applications, without needing to pay attention to the concepts such as easiness, speed, time and location. Due to these advantages, the interest in the e-commerce market is increasing daily in Turkey as it does in the rest of the world, the e-commerce market is also growing rapidly in line with the increasing demand. Through the process of COVID-19, public health is threatened, but also the economy and social life are affected. The process of quarantine and panic environment, which are the effects of a pandemic, affected shopping preferences of the public. The changes in the number of visitors of 4 e-commerce sites operating in Turkey during the COVID-19 period were estimated in this study by artificial neural networks method. The number of visitors of websites were tried to be estimated by using statistical data such as new case, total case, new death, total death, new recovery, total recovery, intubation, intensive care, total test from March 11, which is when COVID-19 was first seen in Turkey, until May 13. The effects of the data that came about during the pandemic process on internet shopping were investigated in the study. The average R² value of the system designed as a result of the test was 90%. Average MSE and MAE values were measured as 0.001 and 0.014, respectively. The fact that these values are close to zero shows that the success of the system is so high. Looking at the results, it can be said that the statistical data during the pandemic process have directly affect online shopping.